2007
DOI: 10.1254/jphs.cp0070063
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of GABAA-Receptor Surface Expression With Special Reference to the Involvement of GABARAP (GABAA Receptor-Associated Protein) and PRIP (Phospholipase C-Related, but Catalytically Inactive Protein)

Abstract: Abstract. GABA A receptors are heteropentameric ligand-gated chloride channels composed of a variety of subunits, including α1 -6, β1 -3, γ1 -3, δ, ε, θ, and π, and play a key role in controlling inhibitory neuronal activity. Modification of the efficacy of the synaptic strength is produced by changes in both the number of neuronal surface receptors and pentameric molecular assembly, leading to differences of sensitivity to neurotransmitters and neuromimetic drugs. Therefore, it is important to understand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 42 publications
(58 reference statements)
0
27
0
Order By: Relevance
“…The upregulation of GnRH secretion in DKO mice might be the cause for the higher levels of LH and FSH in accordance with the hierarchy, but this could not be experimentally qualified because it is difficult to measure serum levels of GnRH streaming in the hypophysial portal system. GnRH neurons were reported to be modulated by activities of GABA A receptors [32], the properties of which have been altered in DKO mice [18,33]. In cases of either dependence on or independence of GnRH, the upregulation of secretion from pituitary glands would be more probable.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of GnRH secretion in DKO mice might be the cause for the higher levels of LH and FSH in accordance with the hierarchy, but this could not be experimentally qualified because it is difficult to measure serum levels of GnRH streaming in the hypophysial portal system. GnRH neurons were reported to be modulated by activities of GABA A receptors [32], the properties of which have been altered in DKO mice [18,33]. In cases of either dependence on or independence of GnRH, the upregulation of secretion from pituitary glands would be more probable.…”
Section: Discussionmentioning
confidence: 99%
“…We also have reported that PRIP modulates brain-derived neurotrophic factor (BDNF)-induced GABA A receptor endocytosis through the regulation of the receptor phosphorylation level (29). These results suggest that PRIP regulates GABA A receptor function through receptor trafficking, phosphorylation, and endocytosis (30,31).…”
mentioning
confidence: 89%
“…Gamma-amino butyric acid receptors (GABA-A) mediate fast synaptic inhibition in the brain and spinal cord (14). Alterations in neuronal surface receptors modulate the synaptic strength, leading to changes in sensitivity to neurotransmitters (15). When a similar network analysis was performed for the 193 control proteins,…”
Section: Proteins Associated With Ic/pbsmentioning
confidence: 99%